2018
DOI: 10.1017/s0033291718001812
|View full text |Cite
|
Sign up to set email alerts
|

Exploring shared genetic bases and causal relationships of schizophrenia and bipolar disorder with 28 cardiovascular and metabolic traits

Abstract: Our findings suggest that SCZ patients may be genetically predisposed to several CM abnormalities independent of medication side effects. On the other hand, CM abnormalities in BD may be more likely to be secondary. However, the findings require further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 99 publications
6
57
3
1
Order By: Relevance
“…In light of the observed association between PRS and binge eating, often associated with greater BMI, our finding that schizophrenia PRS predict lower BMI is difficult to interpret. This association, however, has been previously observed, 35 and is in line with findings of genetic studies showing an inverse correlation between schizophrenia and BMI, 8 and with those of epidemiological investigations showing that low BMI is a risk factor for schizophrenia. 9 The pathophysiological mechanisms underpinning the association between genetic liability for schizophrenia and low BMI are unclear, particularly as clinically, overweight and obesity are more frequently observed in individuals with psychotic illnesses.…”
Section: Comparisons With Previous Literature and Interpretation Of Tsupporting
confidence: 91%
“…In light of the observed association between PRS and binge eating, often associated with greater BMI, our finding that schizophrenia PRS predict lower BMI is difficult to interpret. This association, however, has been previously observed, 35 and is in line with findings of genetic studies showing an inverse correlation between schizophrenia and BMI, 8 and with those of epidemiological investigations showing that low BMI is a risk factor for schizophrenia. 9 The pathophysiological mechanisms underpinning the association between genetic liability for schizophrenia and low BMI are unclear, particularly as clinically, overweight and obesity are more frequently observed in individuals with psychotic illnesses.…”
Section: Comparisons With Previous Literature and Interpretation Of Tsupporting
confidence: 91%
“…However, only one pathway (MAPK-TRK pathway) shared between SCZ and BMI, and two pathways including growth hormone signaling and regulation of insulin secretion signaling shared between SCZ and T2D were confirmed by MAGMA ( Table 2, Supplementary Table S12). Among the three pathways, regulation of insulin secretion signaling was previously reported to be associated with the comorbidity of SCZ and CMD (8). The other pathways can be considered as novel.…”
Section: Common Pathway Identified For the Comorbidity Of Scz And Cmdmentioning
confidence: 99%
“…Historically, the high prevalence of CMD among schizophrenic patients has been primarily attributed to unhealthy lifestyle factors and the side effects of antipsychotic medications (5). However, recent evidences have suggested that genetic basis and common biological pathways shared between SCZ and CMD (6)(7)(8). For example, Andreassen et al using genetic-pleiotropy-informed methods detected 10 loci associated with both SCZ and CVD risk factors, which include waist-to-hip ratio, systolic blood pressure, BMI, LDL, HDL, and TG (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is somewhat surprising given the known phenotypic correlation between schizophrenia and obesity 41 . Nonetheless, three prior reports found significant inverse genetic correlations between body mass index and schizophrenia [42][43][44] , while a fourth reported an inverse, but non-significant relationship 45 . This may suggest that increased rates of obesity among patients with schizophrenia may be a consequence of the disease, potentially due to antipsychotic use or poor support for proper nutrition.…”
Section: Discussionmentioning
confidence: 87%